Parasitic burden in Red panda (Ailurus fulgens Cuvier, 1825) of Illam district Community forest, Nepal - Shrestha, Sajan; Maharjan, Mahendra (Nepalese Journal of Zoology, 2015)
Parasitic diseases pose significant conservation threat in conservation of Red panda. In order to assess the parasitic burden in Red panda of Illam district, Nepal, 14 faecal samples were aseptically collected from community forest of Illam using line transect method following the GPS location. The samples were examined using standard concentration techniques. All the collected samples were found to be positive for both protozoan and helminth parasites. The recorded protozoan parasites includes Eimeria sp., Entamoeba sp., and Balantidium sp. with 64.28%, 57.14% and 14.28% proportion respectively. Similarly the proportion of seven helmithes parasites revealed Oxyuris (100%), Baylisascaris (57.14%), Trichostrongylus (50%), Strongyloides (50%), Trichuris (42.8%), Crenosoma (42.85%) and Hookworm (35.7%). The most of the samples (78.52%) revealed either multiple parasitic infection or triple infection (21.42%) with low to moderate intensity of infection. In conclusion, The parasitic burden in Red Pandas of Illam, community forest is very high hence urgently needs to address this threat in Red panda conservation action plan.